The fundamentals determinants of Singapore Real Estate Investment Trust’s (SREITs) returns : an ARDL approach - Chng, Zhi Rong (2017)
What are the driving forces behind Singapore Real Estate Investment Trust (SREITs) returns? Various empirical research have been conducted on REITs returns. However, the results of the relationship between REITs return and other variables have been inconclusive. Furthermore, limited studies have been conducted on SREITs. This paper attempts to fill the gap by conducting an extensive research on SREITs and develop a conclusive long-run relationship between the variables. Based on the data set from September 2010 to January 2017, the following results are found: (1) Existence of a longrun relationship between SREITs returns and macroeconomic and financial variables. (2) In the long-run, SREITs return co-move with GDP, SIBOR, inflation, Property Price Index and STI. (3) In the short-run, SREITs and the STI co-move. However, SREITs appears to share a negative relationship with GDP and SIBOR. These results suggest that through SREITs, investors could gain diversification benefit and reduce their interest rate risk. In addition, investors could see SREITs as an alternative investment to physical real estate that requires less capital and offers higher liquidity.